Pelayanan Publik Dalam Mewujudkan Reformasi Birokrasi Pemerintahan di Daerah - Sadik, Muh. Nur (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2016)
Civilian apparatus of the state in perfoming their duties as public servants should give priority to the role of managerial and professional bureaucrat administrator and excelled in all areas of goverment. Public services are conducted within the framework of innovation and creativity and the quality of services with high accuracy in accordance with the needs of society. Measuring equipment for measuring the success of public service is a meeting between the services provided by the government with the people's expectations. If the form of service expected by society are not in accordance with the received then lead to public disappointment to the Goverment. To that end, Employee Apparatus State Civil (ASN) at every level of goverment in the center and the area should contribute to public service excellence (quick, easy, inexpensive, precise, definite and accountable) and prioritizes customer satisfaction and needs of the community and consider the level of progress of society.